Meaning-making and intervention in child and youth care practice - Thom Garfat (Scottish Journal of Residential Child Care)
In the past few years the subject of how one makes meaning of one's experiences, or meaning-making, has been a subject of frequent focus in the Child and Youth Care literature in North America (See, for example, Garfat, 1998; Krueger, 1994, 1998; VanderVen, 1992). We do not really know, however, whether meaning is pre-existent, or whether each of us is ultimately the 'author of his or her own life design' (Yalom, 1989, p. 8), creating meaning individually as we move through life. It has generally been accepted in the helping professions, however, that meaning is created as we encounter our experiences (Peterson, 1988; White & Epson, 1990; Watzlawick, 1990) creating for each of us a unique and individualised experience of an event. We also do not know, specifically, how meaning is created by the individual. It appears, however, that culture, personal history, sequencing, and specific circumstance play an important role in determining how one uses one's personal interpretive frame to make meaning of his or her encounters (Bruner, 1990 ; Fulcher, 1991; Goffman, 1974; Guttman, 1991). Each of us, then, brings to the making of meaning our individual experiences.